Peran Mahasiswa KKN-T Dalam Pengembangan Embung Sari Agung Sebagai Destinasi Wisata Edukasi di Desa Ringinagung, Kec. Magetan, Kab. Magetan - Ningrum, Dewi Retno; Andanto, Ramadian Adistya; Sari, Anisa Novita; Komalasari, Belinda; Laily, Devinda Annisa; Rahmatullah, Hasan Ravi; Afifah, Hasna Rifky; Pramudita, Desma Asty; Solichin, Solichin (Edumedia Solution, 2023)
Tourism has become an important milestone in economic development and provides positive impacts, including job creation, increased income and tax contributions. Educational tourism is a program where tourists visit tourist locations to gain direct learning experience. This program combines tourism elements with educational content, creating quality and meaningful activities. Educational tourism is concerned with new learning, cultural knowledge, and application of skills. The popularity of educational tourism continues to grow, for example in foreign language learning. Desa Ringinagung is an example of a tourist destination that has potential in the form of reservoirs and cultural richness. However, the potential of the reservoir has not been optimized as a tourist destination due to the lack of land planning and facilities. The planning process for educational tourism destinations in Embung Sari Agung aims to increase attractiveness, economic value and tourism focus. In this way, the Embung Sari Agung can develop as a tourist attraction that focuses on learning and meaningful experiences.